2012
DOI: 10.1103/physrevlett.108.263906
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Interaction and Synchronization of Oscillating Dissipative Solitons

Abstract: We study the interaction of well-separated oscillating localized structures (oscillons). We show that oscillons emit weakly decaying dispersive waves, which lead to the formation of bound states due to harmonic synchronization. We also show that in optical applications the Andronov-Hopf bifurcation of stationary localized structures leads to a drastic increase in their interaction strength. DOI: 10.1103/PhysRevLett.108.263906 PACS numbers: 42.65.Sf, 47.54.Àr The investigation of localized structures arisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 25 publications
5
51
0
Order By: Relevance
“…Because of the Kerrinduced tilt of the cavity resonance, the detuning, which is measured from the center of the linear (cold) resonance, is correspondingly large. Only a few recent studies have been reported in this regime [5,19,20]. In particular, a fiber cavity experiment has demonstrated that CSs can display periodic oscillations, and preliminary numerical analysis have also revealed various chaotic regimes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the Kerrinduced tilt of the cavity resonance, the detuning, which is measured from the center of the linear (cold) resonance, is correspondingly large. Only a few recent studies have been reported in this regime [5,19,20]. In particular, a fiber cavity experiment has demonstrated that CSs can display periodic oscillations, and preliminary numerical analysis have also revealed various chaotic regimes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, oscillatory dynamics of CSs have been observed in systems without optical feedback: in the Lugiato-Lefever model [47] of a driven optical nonlinear cavity [48][49][50] and in a model of a VCSEL with a saturable absorber extended beyond the mean-field approximation [51]. Furthermore, a period doubling route to chaos has been predicted for localized structures in the Lugiato-Lefever equation [52,53] in a forced and damped van der Pol model [54].…”
Section: Introductionmentioning
confidence: 99%
“…Phase-locking is robust against noise, that was always included in our simulations. This phenomenon could be related to the enhancement of solitons' interaction owing to the Andronov-Hopf bifurcation that makes them oscillate, which was demonstrated for Kerr CSs in [35].…”
Section: × 2 Arrays Of Passively Q-switched Solitonsmentioning
confidence: 99%